Organizational Readiness Analysis Of ERP Transition In PTBA With ADKAR Method (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
PT Bukit Asam (PTBA), a state-owned mining company under MIND ID, is preparing to transition from its Ellipse EAM system to an SAP-based ERP platform. This study assesses PTBA’s organizational readiness for the shift, focusing on both technological and human factors using the ADKAR framework (Awareness, Desire, Knowledge, Ability, and Reinforcement). A mixed-methods approach was used, combining quantitative surveys (47 respondents) and qualitative interviews (6 participants). Results show moderate to strong awareness and desire among employees, reflecting alignment with MIND ID’s strategy. However, gaps in knowledge and ability reveal uneven technical understanding and limited preparedness, especially across generations and departments. Key themes include resistance due to comfort with legacy systems, insufficient training, and weak performance reinforcement. To address these, three business solutions are proposed: (1) a Functional Readiness Task Force (FRTF), (2) a targeted ERP communication campaign, and (3) integration of ERP metrics into departmental KPIs. These strategies are evaluated for impact and feasibility, with fallback options like focus group discussions for low-readiness units. The study contributes theoretically by adapting ADKAR for ERP pre-implementation in a public-sector context, and practically by offering a replicable roadmap for change management. It highlights the critical role of human-centric strategies in ensuring ERP success.
Keywords: ADKAR; Digital Transformation; ERP Readiness; Organizational Change; PTBA; SAP Implementation; State-owned Enterprise